Knowledge and practice regarding emergency contraception among higher secondary students of selected government schools of Godawari municipality. - Karki,Ashmita (2014)
ABSTRACT: Introduction: Unintended teenage pregnancy and abortion is one of the global issues in present context. Emergency contraception is the only post coital method to prevent unintended pregnancy and abortion related complications. Being one of the most appropriate methods of contraception its access and awareness among adolescents is still limited. Objectives: To assess the knowledge and practice regarding emergency contraception among higher secondary students of selected schools of Godawari municipality. Methodology: A descriptive cross sectional study design was conducted. Sample size of the study was 396 students from selected higher secondary schools. Probability sampling technique (lottery method) was used. The semi-structured self administration questionnaire was used for data collection. The data was analyzed using SPSS version 16. Findings: Out of 396 respondents, more than half (67.9%) of the respondents were female and 32.1% were male. The median age of respondents was 17. All most all (97.2%) the respondents had heard about emergency contraception and the most common source was school (48.4%). Only 40.5 % knew about the appropriate time to use ECPs. Minority (1.3%) of the respondents had good knowledge regarding emergency contraception, 21.8% had satisfactory knowledge and 76.9% had poor knowledge. More than half (55.6%) said EC causes abortion. Male had more knowledge as compared to female. Out of 396, only 1.8% of the respondents had practiced emergency contraception. Conclusion: Although all most all had heard about EC and their overall knowledge was poor especially on dose of EC. Minority of the respondents had good knowledge and more than half had misconception regarding emergency contraception which puts them in risk of unintended pregnancy and abortion related complications. Complete education at school should be provided in order to improve knowledge and awareness of EC among adolescents. Key words: Knowledge, Practice, Emergency contraception, higher secondary students.